2007
DOI: 10.1016/j.pain.2006.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala GABA-A receptor involvement in mediating sensory-discriminative and affective-motivational pain responses in a rat model of peripheral nerve injury

Abstract: The contribution of the amygdala to neuropathic pain processing in animals has not been clearly acknowledged. To assess the relative contribution of amygdala GABA-A receptors in mediating sensory-discriminative and affective-motivational pain components, the GABA-A receptor agonist muscimol and the antagonist bicuculline (both 10-25 ng/microl) were administered by acute bilateral injection directly into the central amygdala in rats with a chronic constriction injury (CCI). Escape/avoidance behaviour reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 56 publications
3
75
3
5
Order By: Relevance
“…Decreased neurotransmission in the amygdala, by administration of the Gamma-aminobutyric acid (GABA)A receptor agonist muscimol or lesion of the central nucleus, has been shown to attenuate pain-induced avoidance behaviour i.e. impaired affective processing of pain (Pedersen et al, 2007).…”
Section: Brain Morphology and Electrophysiologymentioning
confidence: 99%
“…Decreased neurotransmission in the amygdala, by administration of the Gamma-aminobutyric acid (GABA)A receptor agonist muscimol or lesion of the central nucleus, has been shown to attenuate pain-induced avoidance behaviour i.e. impaired affective processing of pain (Pedersen et al, 2007).…”
Section: Brain Morphology and Electrophysiologymentioning
confidence: 99%
“…cognitive response to potential but absent threat) in response to aversive stimuli (LeDoux, 1998). Such lesions also attenuate escape‐avoidance behaviour associated with the chronic constriction model (CCI) (Pedersen et al., 2007). Clinical imaging studies have associated evoked pain with regional increases in perfusion in brain areas involved in affective‐motivational control, including the amygdala (Geha et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The amygdala plays a critical role in the emotional response to pain and in pain modulation (Carrasquillo and Gereau 2007;Fields 2004;Gauriau and Bernard 2004;Heinricher and McGaraughty 1999;Ikeda et al 2007;Neugebauer et al 2004Neugebauer et al , 2006Pedersen et al 2007;Rhudy and Meagher 2001). Our previous studies focused on the right amygdala and showed central sensitization and synaptic plasticity in neurons of the latero-capsular division of the central nucleus (CeLC) in an animal model of arthritis pain (Bird et al 2005;Han et al 2005b;Neugebauer and Li 2003;Neugebauer et al 2003).…”
Section: Introductionmentioning
confidence: 99%